2018
DOI: 10.21147/j.issn.1000-9604.2018.03.05
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns for adjuvant docetaxel-based chemotherapy in early-stage breast cancer in China: A pooled retrospective analysis of four observational studies

Abstract: Real-world data revealed that docetaxel/anthracycline combination is the most commonly used category of docetaxel-based adjuvant therapy for patients with operable breast cancer in China; of which TEC is the most frequently used regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…Although a growing body of research showed a declining use of ABC, it is still widely prescribed. The results of a previous pooled analysis of four observational studies demonstrated that 61.9% of the early‐stage breast cancer were treated with ABC together with docetaxel, and our results are consistent with these ones 16 …”
Section: Discussionsupporting
confidence: 91%
“…Although a growing body of research showed a declining use of ABC, it is still widely prescribed. The results of a previous pooled analysis of four observational studies demonstrated that 61.9% of the early‐stage breast cancer were treated with ABC together with docetaxel, and our results are consistent with these ones 16 …”
Section: Discussionsupporting
confidence: 91%
“…Neoadjuvant chemotherapy is a systemic and systemic oncology treatment prior to local breast cancer treatment; it reverses the clinical stage of cancer, inhibits tumor metastasis and resistance to cancer cell drugs, and provides drug sensitivity information and a basis for a rational chemotherapy regimen selection after surgery. A previous clinical trial suggested that neoadjuvant chemotherapy with epirubicin plus docetaxel improved the treatment outcome in breast cancer patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is a common chemotherapy drug for the treatment of breast cancer clinically. 3,4 In the course of administration, he efficacy of this chemotherapy drug is largely limited by various factors. DOX, as a liposoluble compound, features low solubility and poor tissue specificity.…”
Section: Introductionmentioning
confidence: 99%